Critical path of attention to gender-based violence at the Universidad Autónoma Metropolitana (2018-2021) - García Cervantes, Elizabeth (2025)
In this document I seek to address the critical path followed by people in situations of violence in the university environment, that is, the actions taken and the responses found in their search for solutions. Through seven in-depth interviews, the experience of people when moving through various areas and instances of the Metropolitan Autonomous University (Mexico) during the period of 2018-2021 is analyzed, including the office of the lawyer, the Divisional Council/Commission of Misdemeanors, the offices of attention to gender violence and/or the Office of the Defender of University Rights. The results point to the presence of revictimizing practices that limit access to justice in cases of gender-based violence.